Overview of Methods and Strategies for Conducting Virtual Small Molecule Screening. Issue 3 (14th September 2017) - Fradera, Xavier; Babaoglu, Kerim
Abstract: Virtual screening (VS) in the context of drug discovery is the use of computational methods to discover novel ligands with a desired biological activity from within a larger collection of molecules. These techniques have been in use for many years, there is a wide range of methodologies available, and many successful applications have been reported in the literature. VS is often used as an alternative or a complement to High‐throughput screening (HTS) or other methods to identify ligands for target validation or medicinal chemistry projects. This unit does not present an exhaustive review of available methods, or document specific instructions on use of individual software packages. Rather, a general overview of the methods available are presented and general strategies are described for VS based on accepted practices and the authors' experience as computational chemists in an industrial research laboratory. First, the most common methods available for VS are reviewed, categorized as either receptor‐ or ligand‐based. Subsequently, strategic considerations are presented for choosing a VS method, or a combination of methods, as well as the necessary steps to prepare, run, and analyze a VS campaign. © 2017 by John Wiley & Sons, Inc.